2002
DOI: 10.1073/pnas.092327799
|View full text |Cite
|
Sign up to set email alerts
|

Key role of proline L209 in connecting the distant quinone pockets in the reaction center of Rhodobacter sphaeroides

Abstract: T he biological role of bacterial reaction center (RC) membrane proteins is to convert light energy into chemical free energy. The sequential absorption of two photons by the system results into the production of the doubly reduced and doubly protonated form of the ultimate electron acceptor of the complex, a ubiquinone (Q B ). The formed Q B H 2 molecule then delivers its reducing power to the cytochrome bc1 complex, resulting in the release of protons on the periplasmic side of the membrane. The resulting tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
4
15
0
Order By: Relevance
“…The computed proton uptake data in Figure 6 are similar to the experimental values, 25,26 although the shape of the experimental curve is not reproduced exactly. Between pH 4 and 8, Asp L213 and the ubiquinone (see below) almost exclusively account for the shape of the proton uptake curve.…”
Section: Proton Uptake By Q B and The Complete Rcsupporting
confidence: 65%
See 1 more Smart Citation
“…The computed proton uptake data in Figure 6 are similar to the experimental values, 25,26 although the shape of the experimental curve is not reproduced exactly. Between pH 4 and 8, Asp L213 and the ubiquinone (see below) almost exclusively account for the shape of the proton uptake curve.…”
Section: Proton Uptake By Q B and The Complete Rcsupporting
confidence: 65%
“…In RCs isolated in detergent, the formation of Q B¯l eads to substoichiometric proton uptake in the pH range from 5 to 10. [25][26][27][28] At variance, it has been reported that in chromatophores from Rb. capsulatus and Rb.…”
Section: Proton Uptake By Q B and The Complete Rcmentioning
confidence: 94%
“…We have recently reported the stoichiometries of proton uptake by the PQ A -and PQ B -states in the L209PY and L209PF mutants (25). We have shown that the replacement of L209Pro by aromatic residues is likely to affect the functioning of protonation groups lying between Q B and the water phase and which role is to provide protons to the close environment of Q B (i.e., to the ultimate proton donors to Q B (L212Glu and L213Asp)).…”
Section: Discussionmentioning
confidence: 99%
“…The scheme represents the reaction center structure from R. sphaeroides in the quinone region (from (53)). The involvement in the cluster of, at least, L212Glu, L213Asp, L209Pro, M17Asp, L210Asp, M266His, and L234Glu has previously been shown (2,25,30,33,71,85). M249Ala is also mentioned here since it has been shown that when Tyr replaces Ala, its side chain allows it to connect to the interactive network of water molecules and polar residues that spans the region between Q A and Q B on the cytoplasmic side of the complex (29).…”
Section: Appendixmentioning
confidence: 99%